Multiprofessional performance to Prune Belly syndrome: experience report (Research, Society and Development, 2022)
Introduction: Prune Belly Syndrome (BPS) is a congenital disease of unknown origin, characterized by a classic triad: urinary tract changes, cryptorchidism and abdominal muscle deficiency. Because of the varying degrees of implications, treatment and prognosis are defined by the clinical specificity of each patient. Methodology: This article is an experience report that aimed to report multiprofessional assistance to Prune Belly syndrome in a maternal-infant hospital. Experience report: Experienced during the Multiprofessional Residency Program in Women’s and Children’s Health Care in a maternal and child hospital in the State of Pará, in 2022. All health professionals are important to the care of the syndromic patient, in which in the experience the need for qualification of the multidisciplinary team was evaluated, the construction of up-to-date knowledge about Prune Belly syndrome and how pediatric care and care must be provided during the entire period of hospitalization of these patients. Conclusion: The multidisciplinary team should provide a systematic assistance, focused on diagnosis, treatment and immediate intervention as soon as it identifies the signs and symptoms, seeking update and research on the syndrome, improving care and always seeking to improve well-being, a good quality of life and a development of humanized methods to patients with this pathology.